The Impact of Self-Care Education with Teach-Back Method on Self-Esteem in Kidney Transplant Recipients: A Clinical Trial - Masoumeh Hemmati Maslak Pak; Farzin Mollazadeh; Hamidreza Khalkhali; Saeed Abkhiz (Hamadan University of Medical Sciences, 2020)
Background & Aim: Kidney transplantation leads to return to a healthy life and relief from hemodialysis restrictions. The benefits of kidney transplantation have been proven but require constant self-care monitoring throughout one's life and training and support. One of the new methods of training is the teach-back method used to obtain and understand information. This study aimed to determine the impact of self-care education with Teach-Back method on self-esteem in Kidney Transplant Recipients. Methods: In this clinical trial study, 79 renal transplant patients were selected from the clinic of Imam Khomeini Hospital in Urmia in 2016 and were randomly assigned to intervention and control groups. Then, in the intervention group, educational content about self-care with teach-back method was presented during five 60-minute sessions. Data were collected using demographic questionnaire and Rosenberg self-esteem questionnaire. Results:   Before intervention, the mean score of self-esteem was not significantly different between the control and intervention groups (P=0.559). After the intervention, the intervention group had a significant increase in the mean score of self-esteem compared to the control group (P=0.001). Conclusion: In this study, self-care education with teach-back method was effective in improving the self-esteem of kidney transplant patients. And it is suggested to use the teach-back method in education of patients with kidney transplantation.